A Comparative Study of Different Staining Techniques for Cellulase Activity on CMC (Carboxy Methyl Cellulose) Agar - Bambharolia, R. P.; Vyas, Trupti K.; Vavdiya, P. A.; Damasia, D. M.; Garaniya, N. H.; Deshmukh, A. J. (International Journal of Economic Plants, 2024)
The present experiment was conducted at Department of Plant Pathology, College of Agriculture, Navsari Agricultural University, WaghaiduringMarch-October, 2021. cellulolytic bacterial isolates CD11, CD17, CD19, CD22 and CD35 were screened to determine the staining efficiency of various stains for cellulase activity on CMC(Carboxy Methyl Cellulose) agar and it was observed that all the isolates conferred clear zone around the colonies through different staining dyes and bacterial isolate CD35 showed the highest cellulolytic index in all the dyes. The cellulolytic index of CD35 was highest with gram’s iodine (3.34) next in order of coomassie brilliant blue (2.96), safranin (2.55) and congo red (2.15).Significantly, higher cellulase activity was recorded in CD35 (0.169 Uml-1) at 24 hrs after inoculation It was followed by CD17 (0.124 Uml-1), CD19 (0.101 Uml-1) and CD11 (0.081 Uml-1), while it was lowest in CD22 (0.052 Uml-1). Maximum cellulase activity was recorded at 72 hrs after inoculation by all the selected isolates except CD22 isolate, which was maximum 96 hrs after inoculation. CD35 gave significantly maximum cellulase activity (0.822 Uml-1) at 72 hrs after inoculation. Next in order to cellulase activity was CD17 (0.477 Uml-1) which was at par with CD19 (0.471 Uml-1) followed by CD11 (0.292 Uml-1) while, it was lowest in CD22 (0.199 Uml-1).Cellulolytic bacteria CD35 was identified as Bacillus subtilis by morphological, biochemical and molecular methods and submitted to NCBI GenBank database with accession numbers MW715021.